Mathematics
Factorise completely using factor theorem :
6x3 - 11x2 - 3x + 2.
Factorisation
1 Like
Answer
Substituting x = 2 in above equation, we get :
⇒ 6(2)3 - 11(2)2 - 3(2) + 2
⇒ 6(8) - 11(4) - 6 + 2
⇒ 48 - 44 - 4
⇒ 0.
∴ x - 2 is the factor of 6x3 - 11x2 - 3x + 2.
On dividing 6x3 - 11x2 - 3x + 2 by (x - 2), we get :
∴ 6x3 - 11x2 - 3x + 2 = (x - 2)(6x2 + x - 1)
= (x - 2)(6x2 + 3x - 2x - 1)
= (x - 2)[3x(2x + 1) -1(2x + 1)]
= (x - 2)(3x - 1)(2x + 1).
Hence, 6x3 - 11x2 - 3x + 2 = (x - 2)(3x - 1)(2x + 1).
Answered By
1 Like
Related Questions
If matrix P = , find the matrix P + Q.
A(8, 6), B(10, -10) and C(4, -4) are the vertices of triangle ABC. If P is the mid-point of side AB and Q is mid-point of side AC, show that PQ is parallel to side BC also show 2 × PQ = BC.
Prove that : tan2 A + cot2 A + 2 = sec2 A. cosec2 A
In the given figure, triangle ABC is circumscribed by the given circle. Use the given information to find the value of x.